Association Between the miR-146a Rs2910164 Polymorphism and Childhood Acute Lymphoblastic Leukemia Susceptibility in an Asian Population - Zou, Dehua; Yin, Jingwen; Ye, Zhonglv; Zeng, Qiaoli; Tian, Chuan; Wang, Yajun; Chen, Qikang; Chen, Riling (Frontiers in Genetics, 2020)
Background : MiR-146a has been demonstrated to involve in normal hematopoiesis and the pathogenesis of several hematological malignancies through the inhibition of the expression of its targets. Rs2910164(G>C) may modify the expression of miR-146a gene, which might influence the predisposition to childhood acute lymphoblastic leukemia (ALL). However, the inconsistent conclusions reported on the risk of rs2910164(G>C) polymorphism in the childhood ALL susceptibility. Methods: A comprehensive meta‐analysis was performed with available published data under four different genetic models (dominant, recessive, additive and allele models) to derive a more precise estimation on whether miR-146a rs2910164 is an authentic risk SNP for childhood ALL. Results: Six Asian studies including a total of 1543 cases and 1816 controls. We observed a signifi‐cant difference between patients and controls for the additive model (CC vs GG: OR = 1.598, 95% CI: 1.003–2.545,P = 0.049) using a random-effect model. Meanwhile, a trend of increased childhood ALL risk of the dominant model (CC + CG vs GG: OR = 1.501, 95% CI: 0.976–2.307,P= 0.065), recessive model(CC vs GG + CG:OR = 1.142, 95% CI: 0.946–1.380, P = 0.168) and allele model (C vs G:OR = 1.217, 95% CI: 0.987–1.500, P = 0.066) between patients and controls. Conclusions: Our findings suggest that the miR146a rs2910164 polymorphism was significantly associated with a increased susceptibility to childhood ALL in Asian population .